Using Translanguaging as an Intervention for Caribbean Creole Children - Jocelyn, Jessica; Rose, Sulare Telford (Seminars in Speech and Language, 2025)
This tutorial aimed to bridge the gap in the literature by presenting historical and contextual backgrounds on Caribbean Creoles and their speakers while examining the potential benefits and practical implications of incorporating translanguaging into speech-language intervention for children from Caribbean Creole-speaking backgrounds. Utilizing the principles of translanguaging, this tutorial introduces the Translanguaging Speech-Language Intervention Framework (TSI Framework) for clinical speech-language-hearing intervention. The TSI is proposed as a useful tool for working with Caribbean Creole children, though it is applicable to other groups as well. Incorporating TSI into intervention with Caribbean Creole speakers allows for bilingual children to develop and grow their unitary complex language system, equips service providers with a tool to provide culturally responsive service, fosters a strength-based approach for bilingual intervention and assessment, supports families and encourages home language maintenance, and promotes and advocates for linguistic justice.
Keywords: translanguaging; bilingual; multilingual; Caribbean Creole; speech-language pathology